Frequency of Retained Placenta and Common Factors Leading to it Among Patients Presenting with Post-Partum Hemorrhage - Naseem, Sumaira; Mazhar, Tayaba (Indus Journal of Bioscience Research, 2025)
Background: Retained placenta refers to a situation where placenta takes longer than normal to be delivered from the uterus, thereby posing risks of complications like bleeding. This condition has been considered a major cause of severe bleeding in mothers. There are various factors that contribute to this condition, including being a preterm delivery, unbooked, and a grand multipara. Objective: To determine the frequency of retained placenta and identify common factors leading to its occurrence among patients presenting with postpartum hemorrhage. Study Design: Cross-sectional study. Duration and Place of Study: This study was conducted from January 1, 2023, to July 1, 2023 at the Obstetrics and Gynecology Department of Khyber Teaching Hospital, Peshawar. Methodology: A total of 246 female patients, aged 25-50 years, presenting with postpartum hemorrhage were included in the study. Data on demographic details, antenatal care, prior pregnancies, mode of delivery, and potential risk factors for retained placenta were collected. The frequency of retained placenta and factors such as preterm delivery, unbooked status, grand multiparity, previous dilation and curettage, and previous cesarean section were assessed. Statistical analysis was performed using SPSS version 25, and chi-square tests were applied for association analysis (p ≤ 0.05). Results: Out of 246 patients, 37 (15.00%) had retained placenta. The most common risk factors were preterm delivery (78.40%), unbooked status (62.20%), and grand multiparity (56.80%). Statistically significant associations were observed between retained placenta and maternal age ≤30 years (p = 0.005) and parity >2 (p = 0.006). Conclusion: Retained placenta is a significant contributor to postpartum hemorrhage in the studied population. Preterm delivery, unbooked status, and grand multiparity were identified as the most common factors leading to retained placenta.